2013
DOI: 10.1111/joim.12042
|View full text |Cite
|
Sign up to set email alerts
|

At the heart of the arterial baroreflex: a physiological basis for a new classification of carotid sinus hypersensitivity

Abstract: The aim of this review is to provide an update of the current knowledge of the physiological mechanisms underlying reflex syncope. Carotid sinus syncope will be used as the classical example of an autonomic reflex with relatively well-established afferent, central and efferent pathways. These pathways, as well as the pathophysiology of carotid sinus hypersensitivity (CSH) and the haemodynamic effects of cardiac standstill and vasodilatation will be discussed. We will demonstrate that continuous recordings of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 66 publications
1
29
0
1
Order By: Relevance
“…Moreover, this value is consistent with the findings of physiology studies, which have shown that the SBP at heart level at which symptoms because of hypoperfusion occur is 80 mm Hg while standing. 1,3 Nevertheless, an SBP fall below 85 mm Hg also occurs in most patients with an asystolic pause, and virtually, all patients have an associated vasodepressor reflex. A pure cardioinhibitory form does not exist.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, this value is consistent with the findings of physiology studies, which have shown that the SBP at heart level at which symptoms because of hypoperfusion occur is 80 mm Hg while standing. 1,3 Nevertheless, an SBP fall below 85 mm Hg also occurs in most patients with an asystolic pause, and virtually, all patients have an associated vasodepressor reflex. A pure cardioinhibitory form does not exist.…”
Section: Discussionmentioning
confidence: 99%
“…10 In accordance with the Method of Symptoms, carotid sinus hypersensitivity (CSH) was diagnosed when CSM elicited abnormal cardioinhibition (ie, asystole ≥3 s) or vasodepression (ie, fall in SBP >50 mm Hg); CSS was established when spontaneous symptoms (syncope or presyncope) were reproduced in the presence of CSH. 2,3,8,9,11 Owing to its low specificity, CSH alone was not considered diagnostic 1,3,4 because it can frequently be observed in the general older population, 4 and only symptomatic CSH was considered diagnostic. An isolated vasodepressor form was defined when CSM reproduced symptoms with a fall in SBP during at least 1 massage in the absence of asystole ≥3 s. In patients who had baseline asystole ≥3 s, a mixed form was diagnosed when symptoms persisted after the elimination of asystole by means of atropine, and a cardioinhibitory form was diagnosed when symptoms disappeared after atropine 8,9,11 (see Figures I and II in the Data Supplement).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…High prevalence of CSS has also been demonstrated in asymptomatic elderly with no history of dizziness, syncope and falls and therefore the clinical importance of CSS diagnoses is unclear, and it has been suggested that the current criteria are too sensitive [25,28]. Wieling et al have proposed a stricter set of diagnostic criteria for CSS with cut off values of 6 s asystole for cardioinhibitory CSS and a drop in SBP of more than 75 mmHg or to values lower than 80 mmHg for vasodepressor CSS, both of which require reproduction of spontaneous symptoms [29]. Our findings underscores the importance of research into the pathophysiology behind CSS and are in agreement with Wieling et al [29] in their suggestion to implement stricter diagnostic criteria in order to distinguish healthy aging and actual disease.…”
Section: Discussionmentioning
confidence: 99%
“…Wieling et al have proposed a stricter set of diagnostic criteria for CSS with cut off values of 6 s asystole for cardioinhibitory CSS and a drop in SBP of more than 75 mmHg or to values lower than 80 mmHg for vasodepressor CSS, both of which require reproduction of spontaneous symptoms [29]. Our findings underscores the importance of research into the pathophysiology behind CSS and are in agreement with Wieling et al [29] in their suggestion to implement stricter diagnostic criteria in order to distinguish healthy aging and actual disease.…”
Section: Discussionmentioning
confidence: 99%